Analysis of the Peptidoglycan Hydrolase Complement of Lactococcus lactis: Identification of a Third N-Acetylglucosaminidase, AcmC - Huard, Carine (American Society for Microbiology, 2004)
The peptidoglycan hydrolase (PGH) complement of Lactococcus lactis was identified by amino acid sequence similarity searching of the L. lactis IL-1403 complete genome sequence. Five PGHs that are not encoded by prophages were detected, including the previously characterized AcmA and AcmB proteins. Four of these PGHs, AcmA to AcmD, contain a catalytic domain homologous to that of enterococcal muramidase, but they have different domain structures. The fifth one (YjgB) has sequence similarity with the active-site domain of peptidoglycan-specific endopeptidases. The three new PGH-encoding genes identified in this study are all actively transcribed in L. lactis subsp. cremoris MG1363. The relative abundance of their transcripts varied during growth and was maximal during the early exponential growth phase. The three encoded proteins have peptidoglycan-hydrolyzing activities which are detected only at acidic pHs by zymography. Like AcmA and AcmB, AcmC has N-acetylglucosaminidase activity rather than the N-acetylmuramidase activity predicted by sequence similarity.